1993
DOI: 10.1016/0014-5793(93)80058-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CpG island at the 5' end of murine leukemia inhibitory factor gene

Abstract: We identified a CpG island at the 5' end of murine leukemia inhibitory factor gene (LIF). The CpG island is 0.6 kb long and covers most of the first exon and first intron. The region is non-methylated. its G+C content is 65% and relative frequency of CpG dinucleotide is 0.7. The block of 150 nucleotides, which is 72% conserved between murine, human, ovine and porcine genes, is a part of the CpG island. Two DNA fragments from this CpG island interact with nuclear proteins from NIH 3T3 cells. One fragment partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The first region is located between the D-form axon and the M-form exon and is characterized by a high-GC content and regions of sequencing similarity to the human LIF gene. In addition, Kaspar et al (1993) have demonstrated that this region of the LIF gene is hypomethylated in many types of cells and associates with specific nuclear proteins. The authors have argued that the GC-rich region has the properties expected of a CpG 'island' found in the promoter region of many genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first region is located between the D-form axon and the M-form exon and is characterized by a high-GC content and regions of sequencing similarity to the human LIF gene. In addition, Kaspar et al (1993) have demonstrated that this region of the LIF gene is hypomethylated in many types of cells and associates with specific nuclear proteins. The authors have argued that the GC-rich region has the properties expected of a CpG 'island' found in the promoter region of many genes.…”
Section: Discussionmentioning
confidence: 99%
“…The region therefore confers an important requirement for specific genomic locations to permit expression of the LIF gene. The identification of hypomethylated regions in the endogenous LIF gene in this region and binding sites for nuclear proteins (Kaspar et al, 1993) suggest that the action of these proteins may be to repress transcription. It is of interest that the nuclear protein factor has been demonstrated to bind to hypomethylated regions in the GC islands and act to repress transcription Bird, 1991, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation has at least two important implications. First, CpG islands are gene-associated and can be used as markers to identify genes [8][9][10][11][12][13][14][15]. For example, according to the results in [15], about 70% of the identi_ed CpG islands are associated with the human genes.…”
Section: Cpg Dinucleotides and Methylationmentioning
confidence: 99%